Studies on the biology and ecology of telescope snail Telescopium telescopium (Linnaeus, 1758) (Mollusca Gastropoda Potamididae). - Barnuevo, Kyle Dominic E. (2021.)
In the Philippines, Telescopium telescopium is a ubiquitous brackishwater snail that inhabits mangrove areas and aquaculture ponds. It has a large economic potential however, its biology and ecological role in mangrove areas and aquaculture ponds are still understudied. In this study, the telescope snails ovipositor, gut content, and bioturbation potential in sediment quality were observed. Results revealed that a juvenile telescope snail with <35 mm shell length had an undeveloped ovipositor while an adult female snail with >35 mm shell length had a well-developed ovipositor. It was characterized by emphasized microstructures such as major grooves, minor grooves, and a white opaque region adjacent to the ovipositor. The gut content was mainly composed of Cyanobacteria (>50% abundance) followed by green algae, diatoms, andzooplankton. Telescope snails had a positive effect on sediment quality based on pore water pH (ave. increase of 2.88±0.06), dissolved oxygen (ave. increase of 2.25±0.2 mg/l), redox potential (ave. increase of 251±8.38 m V), total organic matter (ave. decrease of 79.72±1.7%) and sulfates (ave. decrease of 13.23±3.6%).
Thesis (M.S. Fisheries - Fisheries Biology). -- [Miagao, Iloilo] : University of the Philippines Visayas, August 2021.
Keywords: Bioturbation; Gut content analysis